Ethnobotany and Natural Products: The Search for New Molecules, New Treatments of Old Diseases or a Better Understanding of Indigenous Cultures? - Heinrich, M.
Results of various projects on Mexican Indian ethnobotany and some of the subsequent pharmacological and phytochemical studies are summarised focusing both on chemical-pharmacological as well as anthropological (ethnopharmacological)aspects of our research. We have identified taste and smell properties of medicinal (vs. non-medicinal)plants as important indigenous selection criteria. There exist well-defined criteria specific for each culture, which lead to the selection of a plant as a medicine. This field research has also formed a basis for studies on bioactive natural products from selected species. The bark of Guazuma ulmifolia showed antisecretory activity (cholera toxin-induced chloride secretion in rabbit distal colon in an USSING chamber). Active constituents are procyanidins with a polymerisation degree of eight or higher. Byrsonima crassifolia yielded proanthocyanidins with (+)epicatechin units and Baccharis conferta showed a dose-dependent antispasmodic effect with the effect being particularly strong in flavonoid-rich fractions. Our ethnopharmacological research led to the identification of sesquiterpene lactones (SLs)like parthenolide as potent and relatively specific inhibitors of the transcription factor NF-kappaB, an important mediator of the inflammatory process. The inhibitory effect of SLs is very strongly enhanced by the presence of such groups as the isoprenoid ring system, a lactone ring containing a conjugated exomethylene group (alpha-methylene-gamma-lactone)and an alpha,beta-unsaturated cyclopentenone or a conjugated ester moieties. Our work also elucidated the NF-kappaB inhibiting activity of the photosensitiser phaeophorbide A from Solanum diflorum (Solanaceae)in PMA induced HeLa cells. Hyptis verticillata yielded a series of lignans as well as sideritoflavone, rosmarinic acid and (R)-5-hydroxypyrrolidin-2-one and is rich in essential oil (rich in alpha-pinene, beta-pinene and thymol). Other species investigated include Begonia heracleifolia, Crossopetalum gaumerii, Epaltes mexicana, Pluchea symphytifolia and Xanthosoma robustum.